Malnutrition and central retinal vein occlusion in a young man - Tuteja, Nupur; Sachdeva, Abhishek; Manjhi, P.K. (International Journal of Research in Medical Sciences, 2017)
Can vitamin B12 and folate deficiency cause central retinal vein occlusion? We conducted a literature search to find out whether nutritional deficiency of vitamin B12 and folate can lead to impaired vision. The patient in the article reported in Ophthalmology, department of MMIMSR, Haryana, India, with complain of gradual painless visual loss over six weeks. He was found to have unilateral central retinal vein occlusion with significant anemia and vitamin B12 and folate deficiency. Vitamin B12 and folate deficiency can lead to elevated levels of homocysteine. We found a large amount of published data relating central retinal vein occlusion to elevated homocysteine levels, but there was a lack of conclusive evidence for this association Patients should be asked about their dietary history where a thrombotic event is suspected or confirmed.